STRATEGI GURU AKIDAH AKHLAK DALAM MENGATASI AKSI BULLYING DI MADRASAH - Humaida, Dinda Amaly Ayyu; Kunaepi, Aang; Perwita, Atika Dyah (UIN Antasari Banjarmasin, 2024)
Aqidah Akhlak teachers are expected to be able to play a role in preventing bullying in madrasas with various efforts to create a safe and peaceful school life. This research was carried out using a qualitative approach with descriptive research using the case study method. Data collection was carried out through a process of interviews, observation and documentation. The results of this research show that: 1) The form of bullying behaviour that occurs at MA Al-Wathoniyyah is verbal and physical, 2) The role of the Aqidah Akhlak teacher in overcoming bullying is by becoming a teacher, guide, counsellor, evaluator, model/example, and as a driver of creativity, 3) Solutions provided by the school as an effort to prevent and overcome bullying by providing understanding, advice and motivation; become a role model teacher to instil morals; enforce madrasa rules and regulations; socialization; and strengthen cooperation between madrasahs and student guardians. Apart from that, some plans are still being pursued to prevent bullying through regularly scheduled mentoring with students. As well as carrying out mandatory monthly meeting agendas in the form of supervision from the madrasa head together with the class teacher and Guidance Counseling. Keywords: Bullying; Moral Creeds; Teacher's Role Abstrak: Guru Akidah Akhlak diharapkan mampu berperan dalam pencegahan aksi bullying di madrasah dengan berbagai upaya demi terwujudnya kehidupan sekolah yang aman dan damai. Penelitian ini dilakukan melalui pendekatan kualitatif dengan jenis penelitian deskriptif dengan metode studi kasus. Pengumpulan data dilakukan melalui proses wawancara, observasi, dan dokumentasi. Hasil pada penelitian ini menunjukkan bahwa: 1) Bentuk perilaku bullying yang terjadi di MA Al-Wathoniyyah adalah secara verbal dan fisik, 2) Peran guru Akidah Akhlak dalam mengatasi aksi bullying adalah dengan menjadi seorang pengajar, pembimbing, konselor, evaluator, model/contoh, dan sebagai pendorong kreativitas, 3) Solusi yang diberikan pihak sekolah sebagai upaya mencegah dan mengatasi aksi bullying dengan pemberian pemahaman, nasihat, dan motivasi; menjadi pribadi guru tauladan dalam rangka penanaman akhlak; menegakkan tata tertib madrasah; sosialisasi; dan mempererat kerjasama pihak madrasah dengan wali siswa. Selain itu terdapat rencana yang masih diupayakan untuk mencegah aksi bullying melalui pendampingan rutin terjadwal serta melakukan agenda wajib rapat bulanan berupa supervisi dari kepala madrasah bersama wali kelas dan guru Bimbingan Konseling. Kata Kunci: Akidah Akhlak; Bullying; Peran Guru